Dual versus single long‐acting bronchodilator use could raise acute coronary syndrome risk by over 50%: A population‐based nested case–control study. (21st July 2021) - Parkin, Lianne; Williams, Sheila; Sharples, Katrina; Barson, David; Horsburgh, Simon; Jackson, Rod; Wu, Billy; Dummer, Jack
Abstract: Background: Coronary heart disease occurs more frequently among patients with chronic obstructive pulmonary disease (COPD) compared to those without COPD. While some research suggests that long‐acting bronchodilators might confer an additional risk of acute coronary syndrome (ACS), information from real‐world clinical practice about the cardiovascular impact of using two versus one long‐acting bronchodilator for COPD is limited. We undertook a population‐based nested case–control study to estimate the risk of ACS in users of both a long‐acting muscarinic antagonist (LAMA) and a long‐acting beta2‐agonist (LABA) relative to users of a LAMA. Methods: The study was based on the primary care PREDICT Cardiovascular Disease Cohort and linked data from regional laboratories and the New Zealand Ministry of Health's national data collections. The underlying cohort ( n = 29, 993) comprised patients aged 45–84 years, who initiated treatment with a LAMA and/or LABA for COPD between 1 February 2006 and 11 October 2016. 1490 ACS cases were matched to 13, 550 controls by date of birth, sex, date of cohort entry (first long‐acting bronchodilator dispensing), and COPD severity. Results: Relative to current use of LAMA therapy, current use of LAMA and LABA dual therapy was associated with a significantly higher risk of ACS (adjusted OR = 1.72; [95% CI: 1.28–2.31]). Conclusion: Dual long‐acting bronchodilator therapy, rather than LAMA mono‐therapy, could increase the risk of ACS by more than 50%. This has important implications for decisions about the potential benefit/harm ratio of COPD treatment intensification, given the modest benefits of dual therapy. Abstract :